1995
DOI: 10.5032/jae.1995.03057
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Agriscience And Natural Resources Curriculum On Students' Science Achivement Scores

Abstract: Over the past several years, poor science test results have increased the demand for improved science education for American students. New and innovative methods of presenting scientific materials are needed to improve student achievement and enthusiasm for learning science. One solution to this dilemma has been to increase students' interest in science by using agricultural and natural resources concepts to teach science. This teaching method incorporated agricultural concepts of plant science, animal science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 4 publications
1
26
0
Order By: Relevance
“…Conners and Elliot (1995, p. 62) also recommend that, "Local school boards should study the possibility of offering science credit for agriscience and natural resource classes that contain a significant amount of science objectives" as a means of increasing science achievement scores. Also suggested in Conners and Elliot's (1995) study was the lobbying of universities to recognize agriscience courses as science credit for enrolling students.…”
Section: Agriscience Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conners and Elliot (1995, p. 62) also recommend that, "Local school boards should study the possibility of offering science credit for agriscience and natural resource classes that contain a significant amount of science objectives" as a means of increasing science achievement scores. Also suggested in Conners and Elliot's (1995) study was the lobbying of universities to recognize agriscience courses as science credit for enrolling students.…”
Section: Agriscience Educationmentioning
confidence: 99%
“…According to Conners and Elliot (1995), the conceptual framework for science achievement should and can very easily incorporate agriscience into the secondary science program. Conners and Elliot (1995, p. 62) also recommend that, "Local school boards should study the possibility of offering science credit for agriscience and natural resource classes that contain a significant amount of science objectives" as a means of increasing science achievement scores.…”
Section: Agriscience Educationmentioning
confidence: 99%
“…In the characteristics, none of the 40 represented a culturally competent teacher of diverse populations. Connors and Elliott (1995) concluded that although students enrolled in agriculture science classes did as well on state science examinations as students not enrolled in agriculture science; however, no increase was apparent with students from low socioeconomic backgrounds. The outcome raises questions if pre-service agricultural education teachers are concerned, aware, or even preparing to teach students who are culturally different (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson (1998) stated that policy makers, educators, administrators, scholars, and social critics have advocated that agricultural education and its approach of integrating scientific academic content in the curriculum has improved the image and quality of high school agriculture programs by meeting the needs and demands of a changing educational system. Connors and Elliot (1995) reviewed research studies showing that agriscience students have performed equally to or better than students in traditionally taught science courses. In fact, at comparable grade levels, agriscience students were leading state science standards compared with students in traditional science classes (Connors & Elliot, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Connors and Elliot (1995) reviewed research studies showing that agriscience students have performed equally to or better than students in traditionally taught science courses. In fact, at comparable grade levels, agriscience students were leading state science standards compared with students in traditional science classes (Connors & Elliot, 1995). More than just attaining equal learning, Connors and Elliot (1995) claimed that science knowledge differs between students who receive traditional science instruction and those who received agriscience-based instruction.…”
Section: Introductionmentioning
confidence: 99%